A stereological study on organelle distribution in human oocytes at prophase I. Issue 3 (14th July 2015) - Pires-Luís, Ana Sílvia; Rocha, Eduardo; Bartosch, Carla; Oliveira, Elsa; Silva, Joaquina; Barros, Alberto; Sá, Rosália; Sousa, Mário
Summary: The ultrastructural analysis of human oocytes at different maturation stages has only been descriptive. The aim of this study was to use a stereological approach to quantify the distribution of organelles in oocytes at prophase I (GV). Seven immature GV oocytes were processed for transmission electron microscopy and a classical manual stereological technique based on point-counting with an adequate stereological grid was used. The Kruskal–Wallis test and Mann–Whitney U -test with Bonferroni correction were used to compare the means of the relative volumes occupied by organelles in oocyte regions: cortex (C), subcortex (SC) and inner cytoplasm (IC). Here we first describe in GV oocytes very large vesicles of the smooth endoplasmic reticulum (SER), vesicles containing zona pellucida-like materials and coated vesicles. The most abundant organelles were the very large vesicles of the SER (6.9%), mitochondria (6.3%) and other SER vesicles (6.1%). Significant differences in organelle distribution were observed between ooplasm regions: cortical vesicles (C: 1.3% versus SC: 0.1%, IC: 0.1%, P = 0.001) and medium-sized vesicles containing zona pellucida-like materials (C: 0.2% versus SC: 0.02%, IC: 0%, P = 0.004) were mostly observed at the oocyte cortex, whereas mitochondria (C: 3.6% versus SC: 6.0%, IC: 7.2%, P = 0.005) were preferentially located in the subcortex and inner cytoplasm, and SER very large vesicles (IC: 10.1% versus C: 0.9%, SC: 1.67%, P = 0.001) in the oocyte inner cytoplasm. Further quantitative studies are needed in immature metaphase-I and mature metaphase-II oocytes, as well as analysis of correlations between ultrastructural and molecular data, to better understand human oocyte in vitro maturation.